0481 Effectiveness of a digital therapeutic compared to medications and cognitive behavioral therapy for treating chronic insomnia in adults. (25th May 2022) - Forma, Felicia; Pratiwadi, Ramya; El-Moustaid, Fadoua; Smith, Nathaniel; Velez, Fulton
Abstract: Introduction: Limitations on the availability of guideline-recommended cognitive behavioral therapy for insomnia (CBT-I) constrain its use and create an unmet need for innovative ways to expand access. Digital therapeutics offer a potential solution. This study compared a digital intervention, traditional face-to-face CBT-I, and prescription medications for insomnia. Methods: Of 184 articles identified in a systematic literature review, 13 studies reported ISI mean change from baseline data: 1 using the digital therapeutic (DT) SHUTi (now known as the prescription digital therapeutic Somryst), 1 on the medication eszopiclone, and 11 on traditional CBT. A Bayesian network meta-analysis (NMA) was performed on the mean change from baseline and the proportion of remitters using the insomnia severity index (ISI) endpoint with follow-up timepoints between 6-12 weeks. Mean change in ISI score from baseline was analyzed as a continuous endpoint while comparisons of the proportion of remitters was performed using odds ratios. The analysis used a random-effects model for the base case analysis. A surface under the cumulative ranking curve (SUCRA) analysis was performed to rank the treatments on each endpoint. Results: Only the DT and CBT-I were significantly different than placebo. The DT had the greatest mean change from baseline in ISI from placebo (-5.77 points, 95% Credible Interval (CrI) [-8.53, -3.07]), followed by CBT-I (-4.3 points, 95% CrI [-6.32, -2.39]). In the SUCRA analysis, the DT had the highest probability (56%) of being the most effective treatment based on ISI mean change from baseline. 8 studies reported the proportion of ISI remitters. Only the DT showed a statistically significant difference in remission vs. placebo, and the DT had the highest odds ratio for remission vs. placebo (OR 12.33; 95%CrI [2.28, 155.91]). The DT had the highest probability (64%), of being the most effective treatment for inducing remission using ISI definitions. Conclusion: The DT in this study was projected to be the most effective therapy on both mean change in ISI and ISI remission within 6-12 weeks of treatment start vs. either traditional CBT-I or medications. Support (If Any): This analysis was funded by Pear Therapeutics, Inc.